Strategi Unggul Konseling Pastoral pada Remaja dalam Hubungan Percintaan - Herman, Samuel (STT Internasional Harvest Tangerang, 2023)
This study is motivated by dynamic changes in the modern adolescent life, particularly in romantic relationships. Examining the complexity of adolescent development, the research aims to explore the effectiveness of Biblical pastoral counseling. The focus is on ensuring the integration of Biblical principles into the daily lives of adolescents. The research utilizes a descriptive qualitative approach, detailing a literature review. Research findings indicate that the use of various methods, including the client-centered approach, establishes a quality religious foundation for adolescents in romantic relationships. In the sequence of these findings, the research highlights that the success of pastoral counseling lies in the counselor's ability to wisely integrate methods, achieving holistic results in guiding adolescents through the challenges of romantic relationships with wisdom.